Data Dissemination Based Clustering Techniques For Vanets : A Review - Hassan, Aslinda; Talib, Mohammed Saad; Hussin, Burairah; Saad Talib, Zainab; M. Sammour, Mahmoud Ahmed; Sabah Rasoul, Zainab (Institute of Advanced Scientific Research, Inc., 2018)
Exploration on Vehicular Ad hoc Networks (VANETs) is still having great consideration by most of the interest researchers.VANET are characterized by its high mobility and various vehicles distributions on roads among other wireless communication networks.The essential purpose of VANET is to exchange safety and entertainment messages among vehicles.VANET environment topology is changing repeatedly due to vehicles high velocity.Such feature will effectively break the communication links between vehicles.It can also rise the routing overhead and reduce the life time of the network.The supreme feasible solution to solve this difficulty is by applying clustering.Clustering is to group the vehicles into sets according to some conditions,rules or characteristics.It also represents an effective methodology to recover the networking protocol scalability.Forming and maintaining suitable cluster to achieve VANETs purposes is creating a big exciting challenge.A stable cluster is indispensable to ensure effective communication among the road vehicles in a dynamic environment.Cluster stability can be achieved by maintaining the Cluster Head (CH) for long possible time,letting the Cluster Members (CM) staying for long duration in the same cluster and reducing the number of CH changes.To improve the cluster stability, Literatures show that mobility-based clustering is one of the best approaches.Certain level of stability can be achieved by taking vehicles density,direction,distances and velocities into consideration.This paper highlights the updated clustering approaches and sheds the light over the related relation between clustering and data dissemination in order to achieve reliable communication among vehicles in VANET’s environment.